Ovidian Phaeton in Dante’s Commedia: Alter Ego and Oppositio - You, Yuze (Quaderni d'Italianistica)

(untitled) (Iter Press, 2023)
As a major mythological source and literary model, Ovid exerts a significant influence on Dante’s mythological narratives in the Commedia. Dante’s reworking of classical narratives exemplifies Ovid’s conception of mythological figures and more. Dante’s dissolution of any doubt about the dominant role of the Divinity and his underlining of the Christian faith are out of the question. However, unlike other Christian poets who focus on the moralization of Ovid’s tales, Dante is more “faithful” to the classical originals. Dante does not, for instance, exclusively read Ovid’s tales in a way that is analogous to those who produce the ordinary didactic moralizations of Ovidian myth in this period. Moreover, having freed himself from the limits of the pervasive moralizing use of Ovid, Dante better preserves the original beauty of Ovid’s writing and also, in a certain sense, its compassion for humans.